The Role of Intellectual and Spiritual Capital in Developing Halal Tourism - Agus Ariyanto; Rifyal Dahlawy Chalil (Proceedings of AICS - Social Sciences, 2017)
The trend of Islamic tourism shows an immense improvement not only in Indonesia but also worldwide. In Indonesia alone, development of Islamic tourism relies on the human factor (intellectual capital) which works in tourism departments as the source of organization. The aim of the research is to test and analyses the role of intellectual capital and spiritual capital in improving the organization performance of tourism department of Aceh. The design of the research is a survey which uses multiple regressions as the data analysis method. The research object is The Tourism Department of Banda Aceh in Aceh Province. Research subjects (respondents) are 75 employees who work at the Department of Tourism City Banda Aceh. The questionnaire (Likert scale) is used as the instrument of data collection with a convenience sampling. The results show that intellectual capital and spiritual capital have a positive and significant impact on the performance of organization. Moreover, spiritual capital plays as the most pivotal in increasing the performance of tourism department of Banda Aceh